Perspectives on Panopolis: An Egyptian town from Alexander the Great to the Arab Conquest : Acts From an International Symposium Held in Leiden on 16, 17 and 18 December 1998 - Egberts, van der; Muhs, Brian; Vliet, van der (Papyrologica Lugduno-Batava, 2002)
Panopolis, the modern town of Akhmîm in Southern Egypt, was in Graeco-Roman times an important religious and cultural centre. Its gigantic temple was a stronghold of traditional Egyptian religion. In Late Antiquity it became a major centre of Hellenistic literature and learning and, at the same time, of Coptic monasticism. The sources for Graeco-Roman Panopolis are numerous and diverse. They not only include numerous texts of all genres in various scripts and languages, but archaeological artefacts too. This volume brings together seventeen contributions, dealing with epigraphy, both hieroglyphic and Greek, Greek papyri, Demotic funerary texts, Coptic literature and local monastic architecture. Without neglecting the heuristic problems which these various sources pose, they conjure up a vivid picture of a world marked by profound religious and cultural change.